2022
DOI: 10.3389/fmicb.2022.912968
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of gut microbiota of term small gestational age infants within 1 week and their relationship with neurodevelopment at 6 months

Abstract: IntroductionSmall for gestational age (SGA) infants are at a higher risk of neurodevelopmental delay than infants appropriate for gestational age (AGA). Previous studies have confirmed that gut microbiota in early life influences subsequent neurodevelopment. However, few studies have reported corresponding data in SGA populations.ObjectiveWe aimed to evaluate the characteristics of the gut microbiota of term SGA infants and the associations between the gut microbiota in SGA infants and neurodevelopmental outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 103 publications
1
6
0
Order By: Relevance
“…In SGA newborns, certain pathogenic and conditional pathogenic bacteria, such as Shigella , Ralstonia , and Clostridium , increased or became the dominant microbiota. Bacteroides fragilis and Clostridium saccharobutylicum were detected in SGA newborns and may be linked to neurodevelopmental outcomes at 6 months ( 44 ).…”
Section: Gut Microbiota and Linear Growthmentioning
confidence: 99%
See 3 more Smart Citations
“…In SGA newborns, certain pathogenic and conditional pathogenic bacteria, such as Shigella , Ralstonia , and Clostridium , increased or became the dominant microbiota. Bacteroides fragilis and Clostridium saccharobutylicum were detected in SGA newborns and may be linked to neurodevelopmental outcomes at 6 months ( 44 ).…”
Section: Gut Microbiota and Linear Growthmentioning
confidence: 99%
“…Lactobacillus and Bifidobacterium have been shown to promote fetal growth, but pathogenic bacteria such as Shigella , Ralstonia , and Clostridium have been found to inhibit baby growth ( 29 , 39 ). Furthermore, particular early-life microbes such as Bacteroides fragilis and Clostridium saccharobutylicum are important for offspring brain development, which can affect baby health and long-term health ( 44 ). As a result, sensible treatments to change maternal or offspring microbiome from pregnancy to early childhood have significant implications for offspring health.…”
Section: Gut Microbiota and Linear Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…The infant acquires a new microbial family due to changes in the gut microbiota and brain developmental stages. Recent study found that a lower gut microbial diversity was associated with a higher risk of neurodevelopmental delay for the small for gestational age (SGA) infants compared with the appropriate for gestational age (AGA) infants [ 56 ].…”
Section: The Molecular Mechanisms Of Gut Microbiota On Brain Developmentmentioning
confidence: 99%